2017
DOI: 10.4236/ojemd.2017.71007
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Disruptors and Fetal Programming

Abstract: The concept "fetal programming" shows who still in the intrauterine life, can interfere in factors related to the genesis and development of diseases in childhood, adolescence and adult life. The literature shows that children born to mothers with gestational diabetes mellitus (GDM) are at increased risk for the development of obesity in adulthood, it becomes fundamental to study more about the subject. Obesity is a disease of multifactorial etiology, resulting from complex interactions between genetic and env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 74 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Since food has begun to be contaminated, especially with pesticides, many of these pesticides behave like estrogenlike endocrine disruptors (Darbre, 2017;Gore et al, 2018). These endocrine disruptors cause the supplementation of adipocytes, so instead of being born with a number of genetically predetermined adipocytes, the fetus will be born with a much higher number (Bateman et al, 2017;Petrakis et al, 2017;Bommarito et al, 2017;Campioli et al, 2014;Lucchese et al, 2017;Kim & Lee, 2017).…”
Section: Obesity Life Cyclementioning
confidence: 99%
“…Since food has begun to be contaminated, especially with pesticides, many of these pesticides behave like estrogenlike endocrine disruptors (Darbre, 2017;Gore et al, 2018). These endocrine disruptors cause the supplementation of adipocytes, so instead of being born with a number of genetically predetermined adipocytes, the fetus will be born with a much higher number (Bateman et al, 2017;Petrakis et al, 2017;Bommarito et al, 2017;Campioli et al, 2014;Lucchese et al, 2017;Kim & Lee, 2017).…”
Section: Obesity Life Cyclementioning
confidence: 99%
“…LBW is not only a determinant of short-term linear growth and survival but it is also a risk factor for later metabolic dysfunction. Endocrine disruptors may limit the function of growth promoting hormones (for example, insulin, inulin growth factors 1 and 2) while aiding the function of growth-inhibiting ones such as glucocorticoids [ 35 ].…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…A recent review of the link between EDCs and obesity observed that prenatal exposure to some of the chemicals lead to decreased birth weight which is in turn linked to disproportionately increased adipose mass after puberty [ 25 ]. As such, EDCs may be involved in foetal programming through hormonal changes that impact birth weight and later risk for non-communicable diseases [ 35 ]. Indeed, a study from India demonstrated that children born small for gestational age were insulin resistant and that poor intrauterine growth predicted higher central adiposity at 8 years of age [ 43 ].…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…Further, individual host factors may affect susceptibility to the ED-induced harmful effects. The developing fetus is in general much more sensitive to endocrine-like perturbations, and exposure to EDs and MDCs in utero may cause irreversible adverse effects that are only evident much later in life and, thus, have long-term adverse effects on human health [23][24][25].…”
Section: Introductionmentioning
confidence: 99%